Cross-species transmission of a novel bisegmented orfanplasmovirus in the phytopathogenic fungus Exserohilum rostratum - Jia, Jichun; Nan, Linjie; Song, Zehao; Chen, Xu; Xia, Jinsheng; Cheng, Lihong; Zhang, Baojun; Mu, Fan (Frontiers in Microbiology, 2024)
Mycoviruses have been found in various fungal species across different taxonomic groups, while no viruses have been reported yet in the fungus Exserohilum rostratum. In this study, a novel orfanplasmovirus, namely Exserohilum rostratum orfanplasmovirus 1 (ErOrfV1), was identified in the Exserohilum rostratum strain JZ1 from maize leaf. The complete genome of ErOrfV1 consists of two positive single-stranded RNA segments, encoding an RNA-dependent RNA polymerase and a hypothetical protein with unknown function, respectively. Phylogenetic analysis revealed that ErOrfV1 clusters with other orfanplasmoviruses, forming a distinct phyletic clade. A new family, Orfanplasmoviridae, is proposed to encompass this newly discovered ErOrfV1 and its associated orfanplasmoviruses. ErOrfV1 exhibits effective vertical transmission through conidia, as evidenced by its 100% presence in over 200 single conidium isolates. Moreover, it can be horizontally transmitted to Exserohilum turcicum. Additionally, the infection of ErOrfV1 is cryptic in E. turcicum because there were no significant differences in mycelial growth rate and colony morphology between ErOrfV1infected and ErOrfV1-free strains. This study represents the inaugural report of a mycovirus in E. rostratum, as well as the first documentation of the biological and transmission characteristics of orfanplasmovirus. These discoveries significantly contribute to our understanding of orfanplasmovirus.